Family Support as a Determining Factor for Medication Compliance in Schizophrenia Patients at the Psychiatric Clinic of Madani Palu Hospital: Dukungan Keluarga sebagai Faktor Penentu Kepatuhan Minum Obat pada Pasien Skizofrenia di Klinik Jiwa RSUD Madani Palu - Istin Istin; Metrys Ndama; Andi Fatmawati Syamsu (Poltekkes Kemenkes Palu, 2025)
Background: Schizophrenia is a chronic mental disorder characterized by cognitive, affective, and behavioral impairments. Patients require long-term antipsychotic treatment, but noncompliance rates remain high and are a major cause of relapse. Family support plays an important role in maintaining patient motivation and adherence to therapy. Research Objective: To analyze the relationship between family support and medication adherence in schizophrenia patients at the Madani Palu Regional General Hospital Psychiatric Clinic. Research Methods: A quantitative approach with a cross-sectional design was used. The sample consisted of 32 respondents who were family members of schizophrenia patients, selected using accidental sampling. The research instruments included a family support questionnaire and the Morisky Medication Adherence Scale (MMAS-8). Data analysis was performed using the Chi-square test with a significance level of 0.05. Results: The study showed that most respondents had good family support (96.9%) and high medication adherence (84.4%). Statistical tests showed a significant relationship between family support and medication adherence in schizophrenia patients (p = 0.002). Conclusion: Family support is an important factor in improving medication adherence in schizophrenia patients. Nursing interventions involving families need to be developed to strengthen the role of families in supporting the success of patient therapy.